2015
DOI: 10.1063/1.4933365
|View full text |Cite
|
Sign up to set email alerts
|

Experimental approaches for studying non-equilibrium atmospheric plasma jets

Abstract: This work reviews recent research efforts undertaken in the area non-equilibrium atmospheric plasma jets with special focus on experimental approaches. Physics of small non-equilibrium atmospheric plasma jets operating in kHz frequency range at powers around few Watts will be analyzed, including mechanism of breakdown, process of ionization front propagation, electrical coupling of the ionization front with the discharge electrodes, distributions of excited and ionized species, discharge current spreading, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 57 publications
1
40
0
2
Order By: Relevance
“…, where is the output signal and is the scatter constant 36,37 . The volume of the plasma column was determined from the Intensified Charged-Coupled Device (ICCD) images.…”
Section: /mentioning
confidence: 99%
“…, where is the output signal and is the scatter constant 36,37 . The volume of the plasma column was determined from the Intensified Charged-Coupled Device (ICCD) images.…”
Section: /mentioning
confidence: 99%
“…The most typical plasma devices operate at 10-50 kHz frequency with the voltage of 2.5 kV-20 kV, applied to the electrode embedded inside of the dielectric tube. The streamer appears over the positive cycle of the applied voltage and propagates inside and outside of the dielectric tube [3,4]. Usually a noble gas is pumping through the dielectric tube since the critical voltage of the breakdown in the noble gases is essentially lower that in the atmospheric air.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In a single plasma jet, the effects of fluid field, electrical field, and device structure on the electrical characteristics, propagation dynamics, and plume length have been widely investigated with optical and electrical diagnosis, ICCD imaging, and Schlieren photography. [18][19][20][21][22][23] It has been found that the plasma plume propagates in different modes, [10,24] there are strongly nonlinear coupling effects of ionization waves determining streamer propagation, [25] the gas heating is the dominant factor for the transition of laminar to turbulent of plasma jet and the plume length, [3,26] and the linear-field and cross-field structures APPJs have also been compared and studied. [27] For jet arrays, there are strong jet-to-jet coupling interactions causing by gas flowing and electrical field from adjacent plasma plumes, which leads to plume divergence, [10,28] different discharge modes, [14,29] and thus affects the downstream plume uniformity and treatment effects.…”
Section: Introductionmentioning
confidence: 99%